PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PAIRED STORY TELLING UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN SISWA KELAS 5 UPT SPF SD INPRES PA'BAENG-BAENG KOTA MAKASSAR - Oktavianingsih, Dwi; Salam, Rosdiah; Sahabuddin, Erma Suryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The main problem in this study is the low writing skills of fifth grade students of UPT SPF SD Inpres Pa’baeng-baeng, Makassar City. This study aims to improve students' writing skills through the application of the Paired Story Telling Cooperative Learning Model for Class V students of UPT SPF SD Inpres Pa'baeng-Baeng, Makassar City. This research method uses Classroom Action Research (CAR) with a qualitative approach. The subjects of the study were 17 teachers and students. Data collection techniques used were observation sheets, tests, and documentation. The results of the study showed that First, the teacher's teaching activities in cycle I, meeting I, were still in the low category and meeting II was in the medium category. Cycle II, meeting I was in the high category, and meeting II was in the very high category. Second, students' learning activities in cycle I, meetings I and II were in the low category. While in cycle II, meeting I was in the medium category, and meeting II was in the very high category. While in cycle II all students had obtained a completeness score according to the KKTP achieved. Based on the results of the study, it can be concluded that the application of the paired story telling cooperative learning model can improve the narrative writing skills of grade V students of UPT SPF SD Inpres Pa'Baeng-Baeng Makassar City. Suggestions for further researchers can be used as references and to conduct research development according to the problems obtained.